The uses of memory in contexts of political violence: The cases of Cambodia and Peru - Todorov, Tzvetan (2024)
The human being is distinguished from the other animal species by the consciousness he has of being inscribed over time. He knows that he is mortal, that his life will have an end, he also knows that it had a beginning which links this initial moment to the present moment. This continuity presents itself to his consciousness in the form of a narrative, rewritten throughout his existence. Human communities do not have a clear image of their birth and even less a prefiguration of their death, yet they act in a manner analogous to that of individuals, except that they are content to transmit narratives concerning the common past, shared by an important part of the population. This awareness of the past is what we call, in a very general sense, individual or collective memory. This text deals with these themes and evokes the cases of political violence in Cambodia and Peru.